FORMAÇÃO CONTINUADA DE PROFESSORES: concepções, discursos e práticas no Programa ARCO - Santos, Eloiza Marinho dos (2007)
This research is about the teachers' continuous development. It emphasizes, as object of study, the Program of Continuous Development for Teachers: Reconstructive Learning of Knowledge - ARCO, designed by a multidisciplinary team of professionals from the Municipal Public School Network in Imperatriz-MA and it was carried out between 2001 and 2004. It evaluates the repercussions of the graduation granted by the program in pedagogical practice for educators, contributing to the re-significance of the continuous development in that county. It analyzes the theoretical-methodological approaches which are its basis, as well as the meaning and repercussions of that graduation experience, starting from the voice and practice of educators. It also investigates the historical-political settlement context of the program. In the dialogic articulation between collected data in the field research and the theoretical study, it seeks in Demo, consultant of the program and main author studied by the faculties, to analyze the main leading axes of the ARCO, such as the research conceptions as educational principles, emancipation and autonomy, these are also based on Paulo Freire, Gramsci and Giroux, who take up the intellectual (conservative and/or radical organic) as mediator, legitimator and producer of ideas and social practices. That latter author works another concept, the one of intellectual transformer. In Helena Freitas we found the defense of the omni lateral conception of the multiple dimensions of the human graduation and of the theory/practice articulation and valorization of the processes of production of knowledge for the investigation and research, in the continuous development. Resulting from a qualitative approach, the aforementioned research chose as subjects: the education manager from the time of settling and implantation of the ARCO, two members of the Base of Assistants Group, four of the Base of Multipliers Group and three participant teachers of the different moments of the graduation (2002, 2003 and 2004). The following procedures were used to collecting data: the study of the Document-base of the ARCO, analysis of the log books written by the teachers, semi-structured interviews and direct observation of the three teachers' educational practice who teach the fundamental school (3rd grade or 4th year, 6th, 7th and 8th grades or 7th, 8th and 9th years). That whole process allowed to assert that the educators of the school network have difficulties in materializing the theoretical-methodological axes worked in the ARCO in their daily practices, due to the short time they tried the methodology, however there is a recognition of the program as formation referencial in a perspective of commitment with the human and political graduation of the students; the textual elaboration and the devolution became frequent in the speeches and practices; they reveal the importance and the need for the continuous development, as permanent space of reflection of the educational practice, orientation, production and socialization of the personal and collectively built knowledge; inclusion feeling into the program; recognition of the self theoretical limitations and the effort to overcome them; change in the conception of evaluation; practice of reflexive records; the conquest of the condition as subject who is known capable to learn, revealed in several initiatives: production and popularization of the elaborated texts, participation in public contests and accomplishment of lectures, interest in studying, research and elaboration resulting in the educators' insertion in graduation, specialization and even master degrees courses. Moreover, we detach the imperious necessity of the definition of Public Politics of Education that include the continued formation as right and necessity of educators of the municipal public net of Empress and that they, in fact, are fulfilled.